International Trade and Corporate Market Power - Gonzalez-Garcia, Jesus; Yang, Yuanchen (Washington, D.C. : International Monetary Fund, 2020)
This paper examines the effect of international trade on corporate market power in emerging market economies and developing countries, with a special focus on sub-Saharan Africa. The analysis is based on a large firm-level dataset, tariff data by sector and agreggate indicators of international trade for the period 2000-17. Greater trade liberalization and trade integration are associated with significant declines in market power, with the effect being more pronounced for firms in the manufacturing and ICT sectors, private sector firms, and firms with higher initial markups. Firms in sub-Saharan Africa tend to experience signficantly lower markups after allowing greater trade integration. The effects of trade liberalization on market power materializes over time, and there are significant complementarities between trade reforms and real sector reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet